A Highly Sensitive Electrochemical Glucose Sensor By Nickel-Epoxy Electrode With Non-Enzymatic Sensor - Riyanto Riyanto (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2016)
The preparation of new sensor for glucose was based on the fact that glucose can be determined by non-enzymatic glucose oxidase. The Ni metals (99.98% purity, 0.5 mm thick, Aldrich Chemical Company) was used to prepare Ni-Epoxy electrode. The Ni-epoxy electrodes were prepared in square cut of 1 cm and 1 mm by length and wide respectively. The Ni metal electrodes were connected to silver wire with silver conducting paint prior covered with epoxy gum. The prepared of nickel-epoxy modified electrode showed outstanding electro catalytic activity toward the oxidation of glucose in alkaline solution. The result from this research are correlation of determination using Nickel-Epoxyelectrode for electroanalysis of glucose in NaOH was R2 = 0.9984. LOQ, LOD and recovery of the Nickel-Epoxy electrode towards glucose were found to be 4.4 μM, 1.48 μM and 98.19%, respectively. The Nickel-Epoxy wire based electrochemical glucose sensor demonstrates good sensitivity, wide linear range, outstanding detection limit, attractive selectivity, good reproducibility, high stability as well as prominent feasibility use of non-enzymatic sensor for monitoring glucose in human urine owing to its advantages of low cost, simple preparation and excellent properties for glucose detection.